Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 206344839 species occurrences available in GBIF matching the query: (Query is too complex. Can be viewed on the landing page) The dataset includes 206344839 records from 15174 constituent datasets: 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 60 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 7 records from BIRDRACE The early birds. 462 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1283 records from RECORD Orthoptera Data. 69 records from Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 19 records from Nannofossil abundance of Hole 60-458. 6 records from Analyses of the recent components of sediment core PS1277-1. 43 records from MEXU/Leguminosae. 28 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 9510 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 177 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 23 records from marine sediment metagenome Metagenome. 651 records from Upper Silesian Museum, Bird Observations. 24 records from Range table from benthic foraminifers in ODP Hole 146-889A. 15 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 82 records from Données naturalistes de Quentin ROME. 354 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 133 records from Bannwald Burghauser Forst. 1 records from SEWBReC Springtails and allies (South East Wales). 1 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 10414 records from SEWBReC Bees, Wasps and Ants (South East Wales). 34 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 1 records from Nannofossil abundance of Hole 9-79. 105 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 16 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 1 records from Benthic foraminifera abundance in ODP Leg 155 holes. 15 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 37846 records from The Himalayan Uplands Plant database (HUP Version 1). 11 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 110 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 40 records from Artenvielfalt auf dem Schulgelände. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 7586 records from Fish specimens of Kagoshima University Museum. 182 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 3634 records from Colecção Entomológica IIA. 439 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 857 records from MZFC/Coleccion de Aves. 2 records from Nannofossil abundance of Hole 10-91. 67 records from DMNS Egg Collection (Arctos). 13019 records from Lepidopterous specimens of Yamagata Prefectural Museum. 44 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 169 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 5555 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 13 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 66602 records from Florida Keys Reef Visual Census 2014. 75 records from An updated checklist of aquatic plants of Myanmar and Thailand. 78 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from BioGIS - Bryophytes - HUJ collections. 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 12773 records from Herbarium Universitatis Daugavpiliensis. 591 records from Colección de Entomología - Curculionidae. 15 records from marine sediment metagenome Raw sequence reads. 27 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 271 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 17610 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 6237 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 10 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5037 records from Swan Coastal Plain Survey. 183 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 11 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 1164 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 2 records from Riedkanal Bötzingen. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 4 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 23 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 3 records from Enrichment metagenome. 263 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 1030407 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 257 records from eDNA_Subseafloor. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 2 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 793 records from Códigos de barras de la vida en peces y zooplancton de México. 10444 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 4 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 338 records from Plant species from the sacred and community forests of Mono departement. 1128 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 3 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 242 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 41 records from Soil metagenome from healthy and unhealthy agricultural soil. 12 records from Collection botanique Lamy de la Chapelle E. (BOUM). 705 records from Brown University Herbarium. 26 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 14 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 77 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 5 records from BIRDRACE accipiter hardcore birding. 4894 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 92 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 24 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 12 records from LISU Herbario Angola. 26 records from nhmc_ob_2019. 304 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 19 records from CNAC/Coleccion Nacional de Acaros. 99 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 23 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1630 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 266 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 127 records from BioAcoustica: Wildlife Sounds Database. 4 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 44 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 316 records from TransForest - vegetation, lichen and fungi data 2016. 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 5 records from Biodiversity of springs and rock seepages 2003. 46 records from Monitoreo de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato-Chocó, 2018. 45 records from CEFS_16S_ITS. 13920 records from Biowide Species data. 1 records from Inventaire et regroupement de données Natura 2000. 106 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 195 records from Schanzenanlage Bergham. 24 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 10 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 8 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 41 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 24 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 2 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 15 records from Schulgelände SGD/Viersen. 582 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 238 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1730 records from Données naturalistes de Ségolène FAUSTEN. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 1705 records from Natural History Museum Maastricht (NL) - Herbarium. 10 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 9307 records from MZL Invertebrate Collections. 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 6232 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 31 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 13955 records from Collection of Coleoptera. 12 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 293 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 43 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 22137 records from Global compendium of Aedes albopictus occurrence. 39 records from Inventaire malacologique de la RNR des Marais de Stors. 75 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 249 records from BioGIS - Reptiles - HUJ collections. 39 records from Teich Berlin Wuhlheide. 6 records from Nannofossil abundance of Hole 27-259. 16 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 1 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 29 records from AKG-Gelände (Bensheim). 225742 records from Flora Atlas N.T.. 42 records from E1 Targeted Locus (Loci). 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 213 records from Fishes in the Argentine Sea from 1967 to the present time. 55 records from Ours 2007 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 311 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 198 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 2 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 95 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 591 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 10698 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 325 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 820 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 550 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 15 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 107 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 97 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 113 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 275 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 35 records from Lebensraum Gesamtschule (Langerwehe). 2 records from Antarctic Amphipoda. 13 records from Foraminifera abundance of Hole 64-481. 3 records from Nannofossil abundance of Hole 29-281. 330 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 81 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 96156 records from Butterflies of Ireland. 79 records from Rare plants database extract from Scottish Natural Heritage. 23 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 333 records from Données des collections d'algues du MNHN. 404 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 905 records from Coléoptères Silphidés du département du Loiret. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 8244 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 10 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 8594 records from National Museum of Natural Science. 437 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 1 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 1 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 19 records from Benthic foraminifera and algae abundance of Hole 81-552A. 13 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 8564 records from University of Guam Insect Collection. 1697 records from National Botanic Garden Belgium - Myxomycetes. 59 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 46 records from Artenvielfalt des "Grünen Klassenzimmers". 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 3 records from BIRDRACE Pfeifenten. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 12 records from Marine metagenome ICM_JRV. 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 416 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 122 records from Museu de Ciències Naturals de Barcelona: BGJBB. 38 records from Données de la naturaliste Laurence Beauchamp. 7 records from Collections ichtyologiques et herpétologiques (BOUM). 54 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 13519 records from Données naturalistes de Bruno OGER. 8206 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1403 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 227 records from UWIZM Molluscs. 65 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 216 records from MCP-Aves - Coleção de Aves. 3 records from NE Scotland fish records 1800-2010. 1 records from Nannofossil abundance of Hole 36-329. 5 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 2 records from Marine sediment metagenome ICM_GMS. 15 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 36 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 1801 records from Collections of Bioclass, school #179, Moscow. 32 records from pyrosequencing Raw sequence reads of deep-sea Archaea. 171 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 17 records from Mycology collection, Norwegian Forest and Landscape Institute. 160 records from Pollen profile ADR353. 2 records from Sächsische Schweiz (Pfaffenstein). 280 records from flower availability 2008 Alb-korrigiert. 85 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 12 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 103 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 36 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 320 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 30 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 1 records from Range table from benthic foraminifers in ODP Hole 161-974B. 173 records from UWIZM Anoles. 382 records from Pat Livermore's Fungus Records 1976 - 2000. 1473 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 9 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 38 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 23 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 330 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 243 records from Macrobenthos Chukchi Sea, 1986. 3 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 21 records from Roter Berg Werdau (Leubnitz). 30 records from Land and freshwater molluscs of Northern Spain. 42 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 1 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 3382 records from Données naturalistes de Charlotte PICARD. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 3 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 1 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 25 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 45628 records from DNV GL Sleipner. 11240 records from University of California Santa Barbara Invertebrate Zoology Collection. 12 records from Faunal assemblage of sediment core TR149-31. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 65 records from Microbial community in marine sediments. 17 records from Naturtag. 47 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from données espèces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 88 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 2935 records from Herbier Louis-Marie (QFA) - Collection de lichens. 8462 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 56 records from CSIRO Yellow Box Fragmentation Project. 43344 records from Entomology Collection at the Natural History Museum of Utah. 1696 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 49984 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 11 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 16001 records from ALCB - Herbário Alexandre Leal Costa. 6 records from BIRDRACE LiLaLau. 1 records from Herbarium specimens of Limoges university (LIMO). 7 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 97 records from Formidabel; Belgian Ants Database. 1239 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 14 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 4 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 125 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 9 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 46 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 6 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 71 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 5 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 223 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 135 records from ABC event data for Nyika Plateau, Buma Hills. 5625 records from CAS Invertebrate Zoology (IZ). 7 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 35 records from water Raw sequence reads. 2 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 27 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 82 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Planktic foraminifera abundance of Hole 14-142. 42366 records from Insects, Outer Hebrides. 1 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 37 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 22 records from An der Ohm, (Wettsaasen). 2 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 15 records from Community structure of Archaea in the western North Pacific and the Arctic Ocean. 185 records from Inventaire des odonates d'intérêt communautaire. 14 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1889 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 1826 records from BioGIS - Vascular plants - Israeli Gene Bank. 642 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 35 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 11 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1405 records from NSW South Coast & ACT plants. 560 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 5 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 18 records from Abundance of birds in the Lena Delta Region. 48 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 3 records from Kirkliston Range stream monitoring. 229 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1177 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 7 records from Ortsrand Zandershagen. 10 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 3 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 4 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 670 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 4684 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 505 records from National Frog Survey of Ireland 2010/2011. 225 records from Colección Ornitológica de la Universidad del Valle. 236 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 2172 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 14 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 260 records from Inventaire naturaliste de la commune de Papaichton (Guyane) : mission 2018. 13 records from Marine Turtles. 9 records from Foraminifera abundance of Hole 33-317A. 651 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 38 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 103 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 40 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 120 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 27672 records from Allan Herbarium (CHR). 6 records from Analyses of the recent components of sediment core PS1011-1. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 7292 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 379 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 9495 records from Royal British Columbia Museum Entomology Collection. 2227 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 68 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 10 records from Antarctic Lakes Brine Raw sequence reads. 1124 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 3 records from Occurrence of mammalia relicts at site Großes Schulerloch. 2 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 118 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 9 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 93 records from Journal of Hymenoptera Research. 1366 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 6 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 3 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 999 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 1281 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2397 records from Colección Entomológica CDMB. 241 records from Données naturalistes d'Olivier LAURENT. 10 records from Uncultured eukaryotes Targeted Locus (Loci). 2739 records from Restauración y conservación de Isla Guadalupe. 16929 records from Lepidoptera (Specimens NRM). 11 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 13 records from Coleção de Coleoptera da Universidade de Brasília. 620 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 30 records from Colección nacional de palmas de Colombia - JBQ. 251 records from ROC RSPB Farmland Species Survey Dataset. 25 records from Warnowtal (Rostock). 6 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 88 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 170 records from Las comunidades de myxomicetes de selva baja caducifolia. 3 records from Wuhle - Brücke / B1. 40739 records from Florida Keys Reef Visual Census 1999. 89 records from Marie-Victorin Herbarium (MT) - Bryophytes. 30 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 52 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 80 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 4 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 27782 records from Collection of saproxylic and xylobiont Beetles. 14 records from Compost microbe establishment and growth in agricultural soils. 13 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 13099 records from National Benthic Inventory. 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 39 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 24 records from Phenological Center - Mushrooms (Karelia). 120 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 4 records from BIRDRACE Die Wendehälse. 22122 records from Tachinid Recording Scheme - GB and Ireland records. 61 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 9 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 73 records from Steinbruch Mainz-Weisenau, 3. Jahr. 13 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 592 records from Inventario florístico de la Sierra de Huautla, Morelos. 55 records from Pollen profile V and Ausfluss at Krumbach, Germany. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 30930 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 7 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 67 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 252 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 55 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 6 records from Wildlife Sightings in the City of Logan. 758 records from Birds Specimens. 16 records from Schulgelände Kranich-Gymnasium (Salzgitter). 115 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 70 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 28 records from Fliegenhaupt Marksuhl. 64 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 2351 records from DMNS Mammal Collection (Arctos). 720 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from Occurrence of mammalia relicts at site Rejtek 1. 27 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 81 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 78 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 85 records from IBF Monitoring of Fungi. 8 records from A comparison of microbial community composition in four contrasting sediments in the Celtic Sea. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 117 records from BenthosChukchiFN762_1976_Falk5. 3 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 3 records from Nannofossil abundance of Hole 15-154A. 24 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 350 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 11 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 110 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 23 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 45 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 97 records from Knechtweide (Kohlfurth). 3232 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 3 records from MCP-Mamiferos - Coleção de Mamíferos. 4 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 19 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 89 records from Meniscus Midges (Dixidae) of Ireland. 12 records from Alien Species in Poland - Animals. 110 records from Occurrence database of native plants and animals of south-central Chile. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 103 records from Natura 2000 Parc naturel régional de Lorraine. 17122 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 2487 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 6 records from Zambian Bat Collections Worldwide. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 4787 records from Vascular plants of south-central China. 6 records from BIRDRACE Punkbirder Helgoland. 70 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 9 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 13 records from Helmintos parásitos de peces del sureste de México. 64 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 12 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Range table from benthic foraminifers in ODP Hole 159-959A. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 45 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 96 records from FFH-Gebiet Klosterwasser/Burkau. 1 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 169 records from Données naturalistes de Hubert GUIMIER. 1805 records from Données naturalistes de Hervé BOUYON. 1795 records from Données de la collection Rousset -1947-2013. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 207 records from Thistle Heads and Ermerged Insects. 89 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 49 records from Amino acid addition experiment Metagenome. 1840 records from Données DREAL Centre-Val de Loire - Faune - 2018. 1008 records from UTEP Invertebrates (Arctos). 7 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 25 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 759 records from Highland bird data 2002 - 2003 - non-breeding records. 1762 records from Harriet Irving Botanical Gardens (HIBG). 181 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 40 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 9703 records from Weed and native flora data for the Swan Coastal Plain. 24 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 11 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 45 records from Uncultured Environmental Isolate Targeted loci environmental. 31 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 20996 records from CNIN/Abejas de México/Apoidea. 342 records from RNF - Données du Parc Naturel Régional du Vercors. 2 records from Crustacea specimens of Kuroshio Biological Research Foundation. 282 records from Flora útil del Municipio de la Huerta, Jalisco. 2965 records from Insectes Hyménoptères Scollidés de France. 26 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 11 records from Ensemble des données Odonates. 9 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 276 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 212 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 282 records from Weddell Sea macrozoobenthos EASIZ I. 21 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 160 records from IOW Natural History & Archaeological Society Marine Records. 1 records from Nannofossil abundance of Hole 10-93. 555 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 78 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 942 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 61 records from Seawater metagenome Targeted loci environmental. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 5 records from Art´n Vielfalt im Kinderwald. 48 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 78 records from Waldi-Weiher. 5 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 9 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 71 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 23 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 16 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 2844 records from MLZ Bird Collection (Arctos). 94 records from Artsprosjekt Pyrenomycetes. 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 42 records from Etude écologique du Parc des Lilas (94). 13 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from Données bibliographiques ASFRA. 23 records from Naturschutzgebiet Müchelholz (Mücheln). 5 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 49 records from Wiese am Waldrand (Gurtweil). 16 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 320 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 4 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 6 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 89 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 29 records from Renaturierung Werse (Innenbereich Beckum). 1974 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 42 records from UWYMV Herpetology Collection (Arctos). 279 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 2927 records from FUEL - Herbário da Universidade Estadual de Londrina. 214 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 291 records from Atlantic Forestry Centre Insect Reference Collection. 2601 records from Midden-Limburg Fish Ponds Survey. 467 records from Dataflos. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 11452 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 10 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 2 records from marine sediment metagenome Raw sequence reads. 12 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 10995 records from Herbarium Senckenbergianum (FR) - Fungi. 836 records from National System of Protected Areas in Poland - Animals. 243 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 2198 records from Seabirds in Norway - Estimated population sizes. 3 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 7 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 7 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 13 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 354 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 580 records from Plant specimens of Bihoro Museum. 10 records from Occurrence of mammalia relicts at site Rusenschloß. 8 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 895 records from Geometridae de France métropolitaine. 947 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 47 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 285 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 3 records from Marine eukaryotes Targeted loci environmental. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 28 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 940 records from Leicestershire and Rutland Aculeate Records. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 355 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 15 records from South Lanarkshire peatland records 2013. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 16618 records from Suivi Temporel des Libellules (STELI). 26 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 1653 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 27 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 40 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 360080 records from First Bird Atlas. 15304 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 10525 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 4 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 30 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 4 records from Ensemble des données Orthoptères. 408 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2602 records from Inventaire de la flore de Charente-Maritime 2018. 938 records from Census of plant species in Pahou forest reserve. 8 records from (Table 3) Relative abundance of selected benthic foraminifera in ODP Hole 104-642C. 9 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 215 records from Pollen profile RAC20, Lake Racou, France. 24 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 222 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1 records from Lepidurus arcticus survey Northeast Greenland 2013. 26 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 710 records from Natura 2000 Vallée de la Seille. 10118 records from Inventario de Hymenóptera; parasítica en México. 35 records from VSN-Wiese. 76 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 19324 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 8275 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 646 records from Ibaraki Nature Museum, Fungi collection. 5 records from 3Soil16S. 1695 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 911 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 8 records from Ecological study of the plankton in the port of Ostend in 1965. 57 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 26639 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 6 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 89 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 6 records from BIRDRACE Nachtigallen. 579 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 4 records from Données naturalistes de THÉVENOT Jessica. 11 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 1 records from Karpfenteich, Klasse 6d. 37 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 845 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 26 records from Ensemble des données Rhopalocères. 3 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 1476 records from Ethnobotanical surveys species in Benin (West Africa). 22 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 85 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 172 records from Benthos Chirnov Basin 1986 and 2002. 235215 records from Queensland Museum provider for OZCAM. 2024 records from Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 1 records from Coccoliths in sediment core GIK23065-3. 36 records from 16S rRNA amplicon from marine Bacteria Raw sequence reads. 138 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 3 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 9115 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 3 records from Range table from benthic foraminifers in ODP Hole 146-889B. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 701 records from Données naturalistes d'Arnaud LE NEVÉ. 351 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 6 records from Analyses of the recent components of sediment core PS1219-1. 47 records from HBRG Invasive Non-native Plants Dataset. 4200 records from Trondheim urban biodyversity survey. 8442 records from Inventaire de la flore de Lot-et-Garonne 2017. 18 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 89 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 99 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 100 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 675 records from Lucanidae. 6457 records from R. L. McGregor Herbarium Lichen Collection. 125 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 24727 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 12 records from Birds Specimens of Akita Prefectural Museum. 1116 records from UAM Fish Collection (Arctos). 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 18 records from Données naturalistes de LE GLOANEC Vincent. 3719 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-71, 1974-5. 1 records from MSUM Ichthyology and Herpetology Collections. 30 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 5 records from Benthic macrofauna abundance of sediment core 13200-008. 45 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 106 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from Nannofossil abundance of Hole 94-611E. 1 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 1849 records from Eurobodalla Regional Botanic Gardens. 15781 records from CABI Africa Invasive and Alien Species data. 14580 records from River Biologists' Database (EPA). 49 records from Selztal bei Friesenheim. 14989 records from Banded Iron Formation and Greenstone survey data. 265 records from Great Eastern Ranges - Slopes to Summit. 530 records from UCM Mammal Collection (Arctos). 125776 records from Tiroler Landesmuseum Ferdinandeum. 79 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 4 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 43 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 89 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 5874 records from Données faune Nature 18 - 2017. 26168 records from Natural History Museum, Vienna - Herbarium W. 6 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8279 records from Quadrige. 3 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 8851 records from Odonata records from RSPB Reserves 1970-2009. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 1 records from Données supplémentaires Atlas des Mammifères marins. 18 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 180 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 1472 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 9 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 7 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 141 records from Protist Diversity in the East China Sea. 31 records from Données espèces - Expertise IPE 79. 2 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1051877 records from NBIS Records to December 2016. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 142 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 128 records from Rohrmeistereiplateau und angrenzendes Gebiet. 435 records from Floral visits on plants, InsectScale 2008. 2 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 1387 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 49 records from South American Antarctic Marine Biodiversity Literature. 51629 records from Arizona State University Vascular Plant Herbarium. 12 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 35 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1027 records from Stoneworts in Wales. 31 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 24 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 112 records from Fungi Collection. 58 records from Naturmiljø Bergensbanen 2015 (project number 616033). 25 records from Données espèces - Expertise IPE 70. 303 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 4 records from Collection Hydrozoa - ZSM München. 1 records from Marine metagenome ICM_AWP. 423 records from Biogeography of near-shore reef fishes in northern New Zealand. 141 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 21 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 90 records from Steinbruch Mainz-Weisenau, 2. Jahr. 5531 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 6154 records from NE Scotland other invertebrate records 1800-2010. 1608 records from ConDidact Citizen Science Surveys - Snails 2006. 8 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 1354 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 18 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 82 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 14 records from Schulgelände (Wetter). 105 records from Deponie Klausdorf. 7 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 14847 records from Données Entomologiques A. HORELLOU 1988-2018. 12 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 173 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 207 records from 2019_NSMK_PL. 232 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 14391 records from Enquête Lucane. 387 records from Erlengraben/Lipp-Tal (Östringen). 2819 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 637 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 3 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 8543 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 203 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 7 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 385 records from Herbier National de Guinée (HNG). 3 records from Benthic foraminifera abundance of Hole 42-379A. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 23 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 397 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 7 records from Benthic macrofauna abundance of sediment core 13077-093. 40461 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 41 records from Isle of Wight non-native invasive species. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 6651 records from Données naturalistes de LUPOLI Roland. 20 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 128 records from Floristic records in the Moscow and Novgorod regions. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 382 records from Weber State University Herbarium. 83 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 4 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 3 records from Données de la naturaliste Anna Even. 11 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 287 records from Données naturalistes de François BRETON. 45 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 1 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 27 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 8 records from Kystfuruskoger i Tysnes og Fusa. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 1047 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 576 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 1 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 12 records from Lepidoptera specimen database of Japan. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 30783 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 12469 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 23 records from Smear slide analysis on sediment core GeoB4214-1. 11 records from Streuobstwiese. 131 records from Collection Vermes - ZMB. 575 records from SIM-Fungal records compiled by Joan Montón. 6 records from BIRDRACE - The famous Grouse feat. The James. 147583 records from Western Australian Museum provider for OZCAM. 27 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 1048 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 43 records from Benthic foraminifera counts of sediment core GIK23352-3. 7 records from Parasitoides de Cochinilla. 64 records from Mamíferos voladores y no voladores del suroccidente colombiano. 21 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 37 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 27 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 44018 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 13 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 230 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 6 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1089 records from Inventaire de la flore du Grand Poitiers 2009. 8 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5 records from Occurrence of mammalia relicts at site Goyet Cave 3. 4 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1414 records from M. Gollop Collection. 12 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 37 records from FBIP: scallop population genetics. 2 records from Coccolith counts of multinet SO119_MSN1272. 1 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 480 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1213 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 54 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 41 records from Schulhof Gymnasium Hürth Bonnstrasse. 8 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 48 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 26 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 2 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 4 records from Society Islands beach bum black flies (Diptera: Simuliidae). 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 15 records from BIRDRACE Bon(n)apartemöwen. 43 records from Nannofossil abundance of Hole 75-532. 187 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 393 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 596 records from NatureMap Calcrete Survey. 25 records from Données naturalistes de BONCHE Jérôme. 25 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 43 records from Benthic foraminifera counts of sediment core PS1852-2. 28 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 2040 records from natagora-earlybirds. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 8 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 10 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 386 records from Hormigas del Museo de Entomología de la Universidad del Valle. 951 records from Elaboration de table de tarif de cubage multispécifique (I). 11 records from Reptiles Specimens of Akita Prefectural Museum. 22 records from UWIZM Snakes. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 15 records from Insect Collections of Okomu National Park- Nigeria. 51018 records from University of Minnesota Insect Collection. 16275 records from ARABEL - Arachnologia Belgica. 8359 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 203 records from Heinersdorfer Sumpfwiese. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 9967 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 3465 records from Arctic Species Trend Index (ASTI) : Marine. 162 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 3866 records from Wolli Creek Preservation Society Bird Survey. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 44 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 1 records from Données naturalistes de Mikaël PAILLET. 12 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 701 records from Données de type contact en Guadeloupe. 171 records from Utah State University, Intermountain Herbarium. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 104181 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 1 records from The Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) of Nepal. 707 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 3 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 237 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 79 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 1421 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 2 records from Benthic foraminifera and algae abundance of Hole 81-554. 14 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 7 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 28 records from Galls on Beech Trees in Hainich, 2008. 5 records from Microbial communities in deep eastern Mediterranean Sea surface sediments. 59 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 52811 records from CAS Entomology (ENT). 93868 records from Carnet B Lorraine. 665 records from Naturalis Biodiversity Center (NL) - Pisces. 10 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 20 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 20 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 48 records from Myxomycetes collection of the University of Eastern Finland. 14963 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 35287 records from Seasearch Marine Surveys in England. 305 records from Annales de la Société Linnéenne de Maine-et-Loire. 34 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 19 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 60 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 232 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 17 records from Données malacologiques continentales de Julien Ryelandt (CORSE 2017). 108 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 2979 records from Collection Trichoptera - SMF. 12452 records from Insectes Hétéroptères Mirides de France. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 59 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 144 records from Range table from nannofossils in ODP Hole 164-994C. 33 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 1552 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from Occurrence of mammalia relicts at site Raj Cave. 358 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 4 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 102 records from Pollen analysis of sediment core GeoB6518-1. 98 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 64 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 84175 records from BLS Mapping Scheme dataset, 1750-2009. 98561 records from Arizona State University Hasbrouck Insect Collection. 87 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 2522 records from Invasive Alien Species Occurrence in Ghana. 49 records from Quarrendorfer Landschaftsschutzgebiet. 193 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 43 records from Registros de quirópteros de tres localidades del caribe colombiano. 237 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 681 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 7 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 434 records from EDP Foz-Tua: Large Mammals (diurnal transects): Ecological Monitoring Program [2011-2017]. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 20 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 219 records from Chironomid remains in the sediment sequence of Site PG1212. 235 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 546 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 39 records from Aves de Caño Cristales, La Macarena, Meta. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 166 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 527 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 72 records from Umgebung der Gesamtschule Hamburg-Winterhude. 6417 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 142 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 6 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 464 records from BUND - Dassower See (Lübeck/Dassow). 20 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 58365 records from Données naturalistes de Monsieur François FOURNIER. 46 records from Birds and plant species near Petushki town (Vladimir region). 22 records from NHMO DNA Bank Other groups collection. 29 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 1648 records from Revues diverses et littérature grise.. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 24 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 79 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 45 records from (Table 4) Thecosomata in ODP Hole 134-831A. 14133 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Sächsische Schweiz (Wehlener Gebiet). 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 1877 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 2 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 7 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 45 records from Expedición Providencia I - INVEMAR. 2 records from Contribution to the tribe Pentoffiini (Cicadellidae: Evacanthinae) with descriptions of two new species and the male of Evanirvana aurea Hill, 1973. 94 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 106 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 5 records from Lindesnes. 778 records from Arthur Chapman Observations. 585 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 281 records from Cuxhavener Küstenheiden. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 10929 records from University of Michigan Museum of Zoology, Division of Birds. 16 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 259661 records from Hatikka Observation Database. 105 records from UWYMV Bird Collection (Arctos). 359 records from Données naturalistes de Monsieur JOURDE Rémi. 165 records from Données naturalistes de AUNEAU Florent. 11 records from Foraminifera abundance of Hole 61-462. 5 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 4 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 133402 records from inatura - Erlebnis Naturschau Dornbirn. 1 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 129 records from Coleoptera identified from the Borax Works, Norman Road site, Bexley, London. 263 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 31 records from Sea water microorganisms Raw sequence reads. 2 records from Amphibian and Reptilian (KIEE-AR). 26 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 25 records from Données de NICOLAS Vincent (SAPROX). 4 records from Brown algae specimens of Komatsu City Museum. 2 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 7 records from Benthic macrofauna abundance of sediment core 13201-002. 60 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 123 records from Inventory of Bassila forest (North-Benin). 2 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 52 records from Pollen profile from Muscotah Marsh B. 94 records from Circumpolar Seabird Monitoring Plan. 40 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 100 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 278481 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 46 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 19764 records from DATAVES. 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 17 records from seawater metagenome Metagenome. 2 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 28 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 590 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 4333 records from Heliconiine Butterfly Collection Records from University of Cambridge. 670 records from The Broward College Insect Collection. 35 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 101 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 11 records from Berea College, Ralph L. Thompson Herbarium. 7 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 28 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 53 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 20 records from Distribution of nanoplankton at trap WR2. 5 records from Birdrace-Bielefinken-Bielefeld. 3306 records from Ecosphère_2017_12_18. 222 records from Fish specimens of Toyama Science Museum. 3366 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 31 records from Müritz-Nationalpark. 62 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 11 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 2034 records from Colección Limnológica Universidad de Antioquia. 8 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 52 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 59 records from Wald am Schloss Wittgenstein Bad Laasphe. 10851 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 302 records from A dataset from bottom trawl survey around Taiwan. 13 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 6 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 1 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 1 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 23 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 1211 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 290 records from Données naturalistes de Renaud PUISSAUVE. 66765 records from Dry Tortugas Reef Visual Census 2010. 9 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 695 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 5 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 76 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 38 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 50 records from The Gibson spider collection. 41 records from Ours 2008 présence Régulière Mailles_10km_LAEA Réseau Ours brun ONCFS. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 142 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 28 records from Naturgrundstück (Eutin). 64 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from The Calliphoridae (Diptera) of Armenia. 651 records from Réseaux écologiques/Trame verte et bleue. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 6 records from données araneologiques de LEENKNEGT Virginie. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 14983 records from Florida Keys Reef Visual Census 1996. 413 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 415 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 47 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 25165 records from Données de l'Observatoire de la Faune de Bourgogne. 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 1203 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 226 records from Fungi of parks, forests and reserves of New Jersey, 2018. 145007 records from Wild bees of Belgium. 116 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 22 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 63 records from Phenological Center - Birds (Murmansk). 32 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 7 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 18 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 7 records from Microbial diversity studies of Arabian Sea sediment. 11 records from Mokihinui and Karamaea small tributaries and seeps. 59 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 16 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 14 records from Echinoderms from the Seaflower Biosphere Reserve. 330 records from If_Ecologie_Conseil_2017_12_18. 39 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 19 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 20 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 4 records from Nannofossil abundance of Hole 49-408. 97414 records from PlutoF platform observations. 377 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 60 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 15 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 13 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 5 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 12 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 28 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 6 records from Benthic macrofauna abundance of sediment core 13078-015. 2 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 15 records from Zoo Frankfurt. 579 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 7 records from BIRDRACE Oostfreesland Bird-Lopers. 178 records from Données Mammifères marins Aquasearch - Dauphin Passion. 3 records from Canada_BasinMegabenthos2002. 186 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 145464 records from Fungal Records Database of Britain and Ireland. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Bulletin d'informations de l'Association française de Lichénologie. 2 records from Nannofossil abundance of Hole 10-89. 549 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 37 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 32 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 15 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 1 records from Description of two new Homoeocera Felder from Guatemala and Mexico (Lepidoptera, Arctiidae, Arctiinae, Euchromiini). 9497 records from La familia Asteraceae en México. Fase VI. 812 records from Regroupement de données Odonates et Lepidotères. 5982 records from WTSWW Data: All Taxa (West Wales). 249 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 6 records from Pollen record of profile 3TZ. 524 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 76464 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 21 records from Données espèces - Expertise IPE 10. 20 records from Marine gastropod distribution from patagonian shallow waters. 46 records from "Ahrschleife bei Altenahr". 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 22 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 105994 records from South Australian Museum Australia provider for OZCAM. 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 23 records from Brock University Herbarium (BU). 14 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 1560 records from SIO Benthic Invertebrate Collection. 1241 records from Whicher Scarp Flora Survey. 867 records from DASSH Data Archive Centre volunteer survey data. 38706 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 230 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 25 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 32 records from Unter hellen Zinnen und finsteren Grotten. 20 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 9 records from BIRDRACE Immerwiederhopf. 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 9 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 1765 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 11 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 3041 records from Modernisation des ZNIEFF du PnrL. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 10 records from Caracterización de Reptiles de las lagunas del municipio del Medio Baudó. 2 records from Collection Malakologie - SMNG. 142 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 1 records from Occurrence of mammalia relicts at site Niederlehme. 229 records from Grand Voyeux - Suivis scientifiques. 3 records from Cryoconite sediments Targeted Locus (Loci). 5 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 23 records from Nannofossil abundance of Hole 67-499. 50 records from Coastal and Marine Species Database. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 12444 records from Carabid Collection (Pinned Vouchers). 200 records from Convention Fédération française de golf - MNHN 2016-2019.. 1247 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 84385 records from Tasmanian Museum and Art Gallery provider for OZCAM. 20 records from TTRS Mammals. 4 records from Weidegebiete in der Selzrenaturierung. 8 records from Occurrence of mammalia relicts at site Veternica. 11 records from Bacterial community dynamics during polysaccharide degradation at contrasting sites in the Southern and Atlantic Oceans. 126 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 331540 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 8 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 312 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 36 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 9 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 3 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 238 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 45 records from Brown bear monitoring data from Deosai National Park. 642 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 34 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 6080 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 8 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 46 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 83989 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 4 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 5013 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 21 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 18 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 989 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 7 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 1 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 15 records from Faunal assemblage of sediment core TR149-32. 5 records from MFS-Plantulas - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Plântulas. 3 records from Nannofossil abundance of Hole 15-149. 1 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 299 records from Registros Primates Neotropicales Convocatoria APC. 76 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 9 records from Benthic foraminifera distribution of sediment core GIK17957-2. 8 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1029 records from Swedish Malaise Trap Project (SMTP) - Pimplinae. 14 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 6 records from Pollen record of profile 3TZ2. 14 records from Invasive Non-Native Species, Outer Hebrides. 69874 records from Phase 2 Lowland Grassland Survey of Wales. 285 records from Gewann Krampf (Heilbronn). 131 records from Naturalis Biodiversity Center (NL) - Crustacea. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 2 records from BMHS Crustacean Collection. 795 records from Lista florística de la Costa Grande del estado de Guerrero. 4 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 29 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 5 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 37 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 65 records from Equatorial Pacific Ocean Targeted loci environmental. 55116 records from MDFRC macroinvertebrate survey. 55 records from Données naturalistes de Pauline BALDUCCI. 27 records from Amtsrain Apolda-Zottelstedt. 2 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 7716 records from DIBA-Parc del Montnegre i el Corredor. 1 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 3 records from Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 166 records from MoJ BioBlitz August 2018. 1214 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 607 records from JRS Wetands data Rwanda, 2019. 1 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 3 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 16257 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 521 records from Inventario de macroalgas de Isla Guadalupe, México. 1 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 632 records from Herbario de la Sociedad Micológica Barakaldo Mikologia Elkartea. 29 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 15 records from Nannofossil abundance of Hole 31-299. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 19 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 10 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 14 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 739 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 5259 records from Inventaire de la flore de Charente-Maritime 2017. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2382 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 27 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 9032 records from MCP - Coleção de Abelhas. 163 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Erhard Sopp. 5 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 1303 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 159 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 25 records from Dorfrand Mauderode. 384 records from SCFS - Sagehen Herbarium. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 4 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 56 records from Shrews of Poland. 169 records from Données du/de la naturaliste Beutin Sabine provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 42927 records from Données naturalistes de Pascal Dupont. 17295 records from K-State Museum of Entomological and Prairie Arthropod Research. 11 records from suivi du site Natura 2000 Carrière Saint Nicolas. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 4279 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 92 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 121 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 16 records from Faunal assemblage of sediment core GS7603-13. 188 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 12 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 2 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 77 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 19734 records from Marine benthic dataset (version 1) commissioned by UKOOA. 13 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 119 records from Freshwater Fishes of Bulgaria. 5350 records from European Moth Nights. 57 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 992 records from Zootaxa. 237 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 1791 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 719 records from NBMB Herps. 45 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 13 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 594 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1 records from Systematics, Morphology and Biogeography Phylogeny of the Augochlora clade with the description of four new species (Hymenoptera, Apoidea). 2141 records from Mollusques dulcicoles de France - Jacques MOUTHON. 329 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 489 records from BID-Malawi-Geometridae-Biodiversity-Data. 359 records from Inventaire et suivi odonate/Fadet des laîches des sites Natura2000 ‘Zones humides de l’étang de Léon’ et ‘Zones humides de l’arrière dune du Marensin’. 10 records from Schulgelände Lise Meitner Realschule (Paderborn). 6 records from Birdrace-Uhulogen-Lippe. 262 records from Collection Aves (bird skins) SMF. 24 records from Revision of Arcastes Baly, 1865 from the Oriental Region (Coleoptera, Chrysomelidae, Galerucinae). 31 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 4363 records from La familia Asclepiadaceae en México. 1 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 7 records from Birdrace-SpeedBirder-Zwickauer_Land. 6 records from Birdrace-Die_Vogelscheuchen-Herford. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 335974 records from Données Observatoire des Papillons des Jardins. 2 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 64 records from JOI - Herbário Joinvillea. 1 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 96 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 2457 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 6 records from BIRDRACE Vogelscheuchen. 16 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 4 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 6 records from Birdrace-Die_Ornithomaten-Herford. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 13 records from Área Galeras - Monitoreo de Aves abril-octubre, 2018. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 2434 records from NINA Vanndata fisk. 3 records from Mammals (UWEP-MM). 1 records from Australian Museum Ichthyology - 2012 Inscription Point. 8 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 1 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 443 records from Inventaires des cygnes du département de l'Eure. 7 records from Landwehrbach. 883 records from CSIRO, fish surveys by the Soela, 1980s. 14 records from Artenvielfalt in der Kinderakademie im RFZ. 20 records from Alien Species in Poland - Plants. 4 records from A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan. 4 records from Microfossil abundance of Hole 16-158. 493 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 358 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 323 records from Données de VINCENT Alexis (SAPROX). 25 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 17 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 4494 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 331 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 14 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 43 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 930 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 16 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8456 records from University Of Pretoria: Lacewing Database Project (1911-2015). 12 records from Freiheitsring (Frechen). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 222 records from USAC Mammals Collection. 19 records from Nannofossil abundance of Hole 66-490. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1428 records from Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 55 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 114 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 615 records from BioGIS - Mammals - SPNI. 159 records from Carnarvon Basin wetland survey. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 394 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 8945 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 2657 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 3 records from South American Coccinellidae (Coleoptera), Part XIX: Overview of Cryptognathini and systematic revision of South American Cryptognatha Mulsant. 3 records from A revision of the Costa Rican species of Stenoeurilla Brailovsky & Barrera (Hemiptera: Heteroptera: Coreidae: Stenoscelideini), with the description of two new species, new distributional records, synonymical note, and key to the known species. 50161 records from SEWBReC Birds (South East Wales). 110 records from Luderbusch. 1698 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 26 records from Teich im Wald zwischen Böblingen und Schönaich. 4 records from Área Galeras - Monitoreo de Aves, 2016. 29 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 1475 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 118 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 7 records from DNA barcoding reveals a species group of the genus Campiglossa (Diptera, Tephritidae, Tephritinae) with recognition of a new species from East Asia and previously unknown females of Campiglossa coei (Hardy). 15 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 13 records from Collection Echinodermata SMF. 1332 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 35359 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 2399 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 1273 records from MfN - Fossil vertebrates IV. 250 records from Fish Collection of Yokosuka City Museum. 286 records from Malawi-Cicindelidae-Biodiversity-Data. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 11 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 399 records from MEXU/Flora de Oaxaca. 3885 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 6 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 60 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 738 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 475 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 33 records from marine sediment metagenome Raw sequence reads. 1 records from Occurrence of mammalia relicts at site Zigeunerfels. 174 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 52 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 20 records from Heavy minerals of sediment core PL94-64. 25 records from Amphibiens filet/Marbotte-Ronval 2013. 13907 records from Amphibiens et Reptiles de France (Enquête 2). 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 465 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 2440 records from Ravensthorpe Range survey data. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 1 records from Schulinnenhöfe (Gelsenkirchen). 60 records from Wirbach-Taubental (Bad Blankenburg). 34 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 2932 records from Données naturalistes d'Alain BERLY. 9871 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 6 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 8 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 25 records from Données opportunistes. 1 records from Nanoplankton abundance at station GeoB2012-5. 5 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 951 records from Auburn University Museum of Natural History Mollusks. 12 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 189 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 2080 records from Yoann_BLANCHON_2017_12_18. 56 records from Inventaire et regroupement de données Natura 2000. 1 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 244 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 152567 records from Données de la flore d’Alsace (SBA). 19 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 3 records from MSB Mammal Observations (Arctos). 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 632 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 11 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 247 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 557 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 8 records from Données naturalistes de Sophie COHEN. 1 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 6 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 1402 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 4608 records from Wikiplantbase #Sicilia. 5 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 116 records from Database of Australasian Vertebrate Occurrences. 12 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 81 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 14 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 9 records from Regroupement de données Oiseaux d'eau du Département des Landes durant les hivers 2016 et 2017. 3 records from Abundance of benthos infauna at station POS128/2_284. 68 records from Phenological Center - Birds (Laplandskiy). 14 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 45 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 498 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 14 records from Benthic foraminifera abundance of Hole 42-380. 24 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 110484 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 4 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 200768 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 3 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 2302 records from Bird records for Argyll for the years 2002 and 2003. 289 records from SWECO. 1924 records from Données naturalistes de Loïc SALAUN. 58 records from MfN - Fossil plants (Paleophytic). 177 records from nsmk_fish_biodiversity_2019. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2 records from Ibaraki Nature Museum, Fish collection. 1144 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 390189 records from Flore Franco-Belge. 8 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 3348 records from EAC - Herbário Prisco Bezerra. 798 records from East Ayrshire Species Database. 490 records from Marine Biological Sample Database, JAMSTEC. 16 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 45 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 9 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 79 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1319 records from Leif Richardson Vermont Bee Specimens. 60 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 53 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 118 records from Données espèces - Expertise IQE 308. 116 records from Données espèces - Expertise IQE 95. 664 records from Collection Crustacea - ZMB. 125 records from The Living Murray Fish data. 94 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 3 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1285 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 26 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 2 records from The identification of the species of the ‘ Spilogona contractifrons species-group’ and the ‘ Spilogona nitidicauda species-group’ (Diptera, Muscidae) based on morphological and molecular analysis. 3834 records from Long-term Bird Census in Cigu 2004-2017. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 49 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 1306 records from CNIN/Tipos Coleoptera. 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 337627 records from Carabidae records for Britain to 2014. 110 records from BARTH-Environnement_2017_12_18. 1 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 688 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2 records from A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran. 144 records from Dermaptera in the icipe collection. 329 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 106 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 25 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 12 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 4 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 658 records from SANBI: DNA Banking(1987-2011). 637 records from The national database for marine data (MADS). 217 records from Naturalis Biodiversity Center (NL) - Mammalia. 261 records from Bacterial Diversity in the East China Sea. 19 records from Foraminifera abundance of Hole 57-440A. 1953 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 9 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 20 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 43 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 6 records from BIRDRACE Enger am Spektiv. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 1 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 12 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 1998 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 6 records from Données naturalistes de CLERGET sylvie. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 3083 records from Regroupement de données "papillons menacés" collectées par les réseaux entre 1990 et 2012. 6 records from Warnowufer Groß Klein. 4 records from Stadtrandlandschaft Apolda-Nord. 592 records from Annotated checklist of the Hemiptera Heteroptera of the Site of Community Importance and Special Area of Conservation “ Alpi Marittime ” (NW Italy). 3477 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 139 records from Données du naturaliste Christian Desmier. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 10 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 8 records from Avifauna asociada a las fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 836 records from Odoanta of Akwa Ibom State University, Nigeria. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 80 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 15 records from Occurrence of mammalia relicts at site Geißenklösterle. 2312 records from Données naturalistes de Bernard Lalanne-Cassou. 20 records from Données naturalistes de Franck NOEL. 6 records from Nannofossil abundance of Hole 82-558A. 1317 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 17 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 7 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 1 records from CSLA - Cal State LA Herbarium. 11 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 286 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 16 records from Nannofossil abundance of Hole 49-410. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 11274 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 23037 records from Alterra (NL) - Entomofauna inventory in peat swamps. 72392 records from Florida Keys Reef Visual Census 2010. 10 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 1957 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 3 records from Two new Exilisia Toulgoët, 1958 from mainland Africa (Lepidoptera, Erebidae, Arctiinae). 4 records from Leicestershire and Rutland Mature trees Inventory 2011. 14 records from Pollen data of trap CB4. 9 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 1 records from Nannofossil abundance of Hole 66-493A. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 4 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 6 records from Rare vascular plant species in North-West of Kostroma region, Russia. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 45 records from Draubiotop Lavamünd. 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 82 records from Extracellular DNA marine sediment Targeted Locus (Loci). 388 records from Netzfluegler_Raw1. 42 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 64 records from "Schwarzwassertal" bei Pobershau. 3 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 11 records from marine metagenome Targeted Locus (Loci). 129 records from Plan de vertebrados de la Patagonia. 46 records from Springtales from lichen communities at Kollåsen in Norway. 6 records from Birdrace_TerraCamper-Münster. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 3 records from AlgaTerra. 326 records from Records from the South Australian Seed Conservation Centre. 82216 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 2 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 52 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 515 records from Danielsberg (Mölltal, Kärnten). 23 records from MfN - Fossil vertebrates III. 7 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 9348 records from LPO_PACA_2017_12_18. 106 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 122 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 10 records from Borkhart. 204 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 5 records from HSU Vertebrate Museum Mammals Collection. 38 records from Targeting a portion of central European spider diversity for permanent preservation. 1 records from Nannofossil abundance of Hole 9-80. 356 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 583 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 217 records from ADDOMEx. 2457 records from Census of species recorded during phytosociological surveys in Benin. 2149 records from 2019_NSMK_PL_2. 8 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 185 records from Foreign plant germplasm collections in Ghana. 8 records from Foraminifera abundance of Hole 57-440B. 2 records from 成龍溼地魚類生態紀錄. 39 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 96 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 240 records from Informatisation des carnets de terrain de Georges Catherine. 1 records from UCYN-A diversity in the Pacific. 5 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 66 records from Moluscos Marinhos de Augusto Nobre. 114 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 95 records from Inventaire et suivi Avifaune. 77 records from Botanic Garden of the Finnish Museum of Natural History. 47 records from Poissons et Crustacés d'eau douce de la Martinique. 676 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 75 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 4427 records from LACM Invertebrate Paleontology. 23 records from Ice Wedge Polygon. 5 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 1089 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 64 records from CG04_2017_12_18. 101 records from Composition of the coccolith flora in sediment core GeoB1710-3. 532 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 128 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 362 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 9 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 11 records from Collection Ephemeroptera - SMF. 510 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 1052 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 5 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 996 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 283 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 2 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 89114 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 108 records from Swedish Malaise Trap Project (SMTP) - Strepsiptera. 399 records from Occurrence data of tree species for crystalline Mountain Forest of Tanzania.. 14 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 887 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 156 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 3277 records from Database for alien invasive plants occurrences in Germany. 243 records from Capture of Primary Biodiversity Data for West African Plants. 2 records from Revision of the amphiamerican genus Mysidium Dana, 1852 (Crustacea: Mysida: Mysidae), with descriptions of two new species and the establishment of two new subgenera. 1 records from Two new species and new record of Amphinemura (Plecoptera: Nemouridae) from northern China. 21 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 83 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 85 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 1000 records from 成龍溼地鳥類生態紀錄. 1 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 39 records from MVZ Hildebrand Collection (Arctos). 44 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 24 records from Overview of the bee genus Trachusa Panzer, 1804 (Hymenoptera: Apoidea Megachilidae: Anthidiini) from China with description of three new species. 377 records from Spider (NSMK-SP). 815 records from OUPR - Herbário "Professor José Badini". 382 records from Inventaire Faune Flore du Cirque de l'Essonne. 357 records from Flore des reliques forestières de la commune de Dangbo. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 7167 records from National Biodiversity Data Bank. Observation records, 1900-2014. 94 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 23 records from VFD-H: Heidenrod: Pferdeweide Mürth. 11701 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 42 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 2 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 162 records from California State University, Long Beach Mammals. 15 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 1638 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 24 records from Nottekanal, Klasse 7 - 10. 56 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 29 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 3 records from Nannofossil abundance of Hole 37-333. 18 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 2 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 3 records from Inventaire des Mollusques Sphaeriidae de France. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 2351 records from données aranéologiques de CORNIC Jean-François. 8 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 48 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 58 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 20 records from Données espèces - Expertise IPE 69. 10 records from Waldwiese. 6 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 1 records from Nannofossil abundance of Hole 24-231. 422 records from Clare Biological Records Centre Dataset 2004-2007. 49 records from Expédition Karubenthos 2012 : données issues des publications. 423 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 6951 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 167 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 14 records from Neotropical Acanthoderini (Coleoptera, Cerambycidae, Lamiinae): Synonymies and new status in some genera, new species, transferences and new distributional records. 3 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 5 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 9 records from Flora und Fauna im Brexbachtal. 2007 records from Senckenberg - CeDAMar Resource. 4826 records from MICROBIS database. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 6 records from Birdrace-Professorenteam-Münster. 294 records from Ontario Breeding Bird Atlas 1981-1985. 11 records from Inventaire de la flore de la Vienne 2011. 1153 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 173 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 248680 records from Swiss National Orthoptera Databank. 110 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 987 records from Données naturalistes de Laurent KREMMER. 4 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 233 records from Biological Collection, National Institute of Oceanography, Goa, India. 2224 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 1249 records from BIOWIDE eDNA Fungi dataset. 10 records from Pollen profile II/B at Krumbach, Germany. 255 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 329 records from Palynological analysis of sediment core GeoB3910-2. 45 records from Steinbruch Mainz-Weisenau. 145 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 9216 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 527 records from Fauna y flora del municipio de Lipa, Arauca. 12635 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 18 records from Macroalgas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 1 records from Japanese Pseudosmittia Edwards (Diptera: Chironomidae). 93 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 4 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 2271 records from Vermont Buprestidae Survey. 5 records from Birdrace-WdW-Wilder_Westen-Viersen. 8462 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 338 records from MPM Milwaukee Public Museum Herbarium. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 107 records from Collection ornithologique A. Maës. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 213 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 314 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Mammal specimens of Komatsu City Museum. 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 6 records from Three new Cryptochetum Rondani, 1875 (Diptera: Cryptochetidae) from Yunnan Province, China and an identification key to Chinese species. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 10 records from Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 27 records from ACT and Southern Tablelands Weed Spotter. 490 records from Report on the Danish Oceanographical expeditions 1908-1910 to the Mediterranean and adjacent seas - Pelagic Polychaetes. 20891 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 11 records from Örtzemündung (Stedden). 18 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 1075 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 46509 records from National Stag Beetle Surveys (Great Stag Hunts). 391279 records from Eremaea. 26 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 4416 records from Marine Offshore Seabed Survey data held by JNCC. 3789 records from KUBI Ornithology Collection. 744 records from FrogWatch SA. 4 records from Nanoplankton abundance at station GeoB2006-4. 4 records from Données naturalistes de Françoise SERRE-COLLET. 44 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 382 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 1230 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 18184 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 90 records from Swedish Malaise Trap Project (SMTP) - Pallopteridae. 5 records from Ackerrain Plönhagen. 1046 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 1004 records from Données odonates. 222 records from Malawi-Histeridae-Biodiversity-Data. 155 records from Biologische Station im Kreis Wesel. 63 records from Schiller Gymnasium Hof 10b. 59 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 18 records from Données du/de la naturaliste Mallard stephane provenant de la base de donnée du SINP Île-de-France CETTIA. 79 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 590 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 8 records from The Apterygota collection (EA) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3718 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 304 records from Rutilans. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 235 records from UTEP Insects (Arctos). 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 3 records from Occurrence of mammalia relicts at site Bivak Cave. 292 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 202 records from Leicestershire Bryophyte Data. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 3 records from Données naturalistes de DURON Cyril. 2049 records from Collection Pisces SMF. 2 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 37 records from Pelagic Gulf of Mexico Targeted loci environmental. 31 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 98 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 320 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2016. 339 records from Packer Collection /Madagascar. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 2224 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 51 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 62 records from Landschaftspflegehof (Berlin). 140 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 5 records from Bachpatenschaft Beeke. 12 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 5490 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 36 records from SPC CoFish Invertebrates Observations Niue 2005. 681 records from Gemeinde Sursee. 2 records from Revision of the Scopula dubernardi species group: how many species? (Lepidoptera: Geometridae, Sterrhinae). 6 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 505 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 1224 records from Insect specimens of Omogo Mountain Museum. 26 records from Nannofossil abundance of Hole 67-496. 440 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 30 records from marine metagenome. 1 records from The genus Toxoneura Macquart (Diptera, Pallopteridae) of the Oriental Region. 66 records from Artenvielfalt auf den Elbwiesen (Dessau). 129 records from Données naturalistes de Daniel PAVON. 462 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 219 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 3 records from On the taxonomy of the genus Pseudacronicta Kononenko, 2001 (Lepidoptera Noctuidae, Acronictinae): the identity of Acronicta omihsiensis Draeseke, 1928. 85 records from Données de la naturaliste Clélie Granger. 162 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 36 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 3 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 2 records from Inventario de Mamíferos Mámbita. 3 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 11870 records from Canadian Museum of Nature Mammal Collection. 27 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 4 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 36 records from Pollen and spore abundance of Hole 42-381. 97519 records from Estonian Nature Observations Database. 40 records from Naturpark Sternberger Seenland. 50 records from Eastern offshore environmental monitoring of Krishna Godavari Basin Bay of Bengal 2013-2016, Funded by: ONGC India. 4863 records from Botanical Museum, Copenhagen, Mycology Herbarium. 363 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 6 records from Birds (NMNO-BI). 177631 records from Biodiversitätsdatenbank des Landes Salzburg. 1837 records from NCSM Mammals Collection. 1 records from Mesozooplankton - Crustacea from the South Adriatic Sea. 91 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 457 records from DMNS Parasite Collection (Arctos). 154 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 20 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 14 records from Nivå Bay species list, Zealand, Denmark. 516 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 4 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 1453 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 7 records from Nannofossil abundance of Hole 64-476. 4230 records from Données naturalistes de Matthias COLIN. 173 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 1576 records from Colección general del plantas vasculares del Herbario JBB. 71162 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 12211 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 8 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 297 records from Cowan Tetrapod Collection - Herpetology. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 67204 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 307 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 10 records from Phytoplankton abundance at station CD46_0705C#4. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 93 records from CASES2003_2004. 95 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 6 records from Hemmerder Schelk (Unna). 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 12918 records from Fife Nature Records Centre combined dataset. 132 records from First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges. 1 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from Notes on the genus Kosmiomiris Kirkaldy (Hemiptera: Miridae: Hyalopeplini) with description of a new species. 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 14 records from CHAS Botany Collection (Arctos). 24 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 482 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 4 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 429 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 8 records from jamaica_invasive_alien_species. 36 records from Naturschutzgebiet Lochbusch-Königswiesen. 824 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 18 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 2 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 2 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 3 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 6755 records from Odonata de Veracruz. 3 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 15 records from BIRDRACE Niederlausitz-Team. 18 records from Cnidaria. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 53 records from Schulgarten Huttenheim (Philippsburg/Baden). 3 records from Bachabschnitt der Nette (Osnabrück). 114 records from Pollen profile from Seminary School Basin. 79392 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 2 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 14 records from BIRDRACE Gätkes Erben. 2 records from A new species of Cryptoperla Needham, 1909 (Plecoptera: Peltoperlidae) from Guangxi of China, based on male, female, and larval stage. 12 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 71 records from Revision of the Eurybrachidae XIV. The Australian genera Olonia Stål, 1862 and Stalobrachys gen. nov. (Hemiptera: Fulgoromorpha). 16 records from Fish (KIWE-PI). 209 records from Benthos counted on dredged samples during Valdivia cruise VA53. 4 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 306 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 106 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 1894 records from Carabidae of the European North-East of Russia. 175 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 6 records from BIRDRACE federleser. 1439 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 78 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 501 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 37 records from The Fishery Grounds near Alexandria.VII.Decapoda.By Heinrich Balss.(1936).Notes and memoirs No. 15. 8 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 24 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 13 records from Banco de Semillas de Boyacá. 9 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 27841 records from CAS Botany (BOT). 8 records from Otiorhynchus (Choilisanu s) theophrastus sp. nov. from Lesbos Island, Greece (Coleoptera, Curculionidae, Entiminae). 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 116 records from CCA_pathobiome. 7 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 465 records from Données naturalistes d'Anaïs MAS. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 15 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 29 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 1 records from (Table 1) Abundance of live benthic foraminifera in surface sediments of the Arctic Ocean. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 10 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 2081 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 9 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 52 records from Flux data of NU2_trap (Table A1). 126 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 382299 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 2 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 1274 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 70 records from Bishop's University Insect Collection (BUIC). 900 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 40 records from Sediment metagenome. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 201629 records from BioFokus. 2860 records from Anymals+plants - Citizen Science Data. 25 records from Chronicle of Nature - Phenology of Insects of FSBI Zeya State Nature Reserve. 634 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 526 records from Tartu University fossil collections. 42 records from MFS-Frutos - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Frutos. 4 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 75 records from Données avifaune de Guadeloupe. 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 2 records from First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species. 24 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 6 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 38 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 543 records from UMNH Reptiles and Amphibians Collection (Arctos). 15 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 63 records from CNAN/Scorpiones. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 11562 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 8 records from BIRDRACE Di-Bi-Di-Birder. 255 records from DBG Tissue and DNA Bank. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 1425 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 100 records from Collection de C.C.H. Jongkind aux Monts Nimba. 45 records from Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 195 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 4 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 5 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 42 records from Gulf of Mexico open ocean Targeted Locus (Loci). 142 records from Pollen profile Märchenwald B, Harz, Germany. 7 records from Nannofossil abundance of Hole 20-200. 203 records from Thistles species and abundance. 5746 records from Mollusca of Costa Rica (INBio). 4 records from Two new species of Prionomastix Mayr (Hymenoptera: Encyrtidae) with a key to Indian species. 2 records from Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil. 1855 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 762 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 15647 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 661 records from Flora vascular acuática de la cuenca del Río Tamesí. 8 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 255 records from flower availability 2008 Hainich. 31 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 169 records from Observations de syngnathes en France métropolitaine. 62 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 39644 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1939 records from Andes to Amazon Biodiversity Program. 696 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 111 records from Données naturalistes de Stéphane ORIO. 13 records from Collection Echinodermata - ZMB. 1 records from Immature stages of American Prioninae Latreille, 1802: descriptions and phylogenetic considerations in Cerambycidae Latreille, 1802 (Coleoptera). 48 records from Miljodir_naturtypekartlegging_2017. 7 records from A description of four new species of fleas (Insecta, Siphonaptera) from Angola, Ethiopia, Papua New Guinea, and Peru. 60 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 7 records from Inventario herpetofaunístico del noroeste de Hidalgo. 68 records from WildesMoor bei Schwabstedt. 59 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from A new subspecies of Glabroculus elvira (Eversmann, 1854) (Lepidoptera, Lycaenidae) from the Dzhungarian Gobi desert, Mongolia. 209 records from Museums-Birds-Biodiversity-Records. 366 records from ZooplanktonBeaufortSeaNOGAP2. 1962 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 3951 records from CPAP - Herbário CPAP. 6 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 7 records from Freshwater Gastropods of Taveuni. 21 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 618 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 6 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 4 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 10 records from Marine sediment Raw sequence reads. 7 records from Benthic macrofauna abundance of sediment core 13200-045. 61 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 373 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 4 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 60 records from Wichita State University Collection. 69 records from Données naturalistes de Pierre-Alexis RAULT. 9386 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 16913 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 35 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 2 records from Dark ocean microbial diversity. 11 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 17 records from Nannofossil abundance of Hole 94-606A. 270 records from pbzt_insect_biodiversity. 81 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 148 (N.S) n° 41 (1), 2013 - Données faune. 8 records from Insect specimens of Himeji City Science Museum. 4 records from Ohio University Invertebrate Paleontology Collection. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 40 records from NZCS Upper Tapanahony Expedition 1991. 5 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 8 records from Tanzanian Vertebrate Collection. 715 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 12 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 3 records from Revision of Camarota Meigen (Diptera: Chloropidae), with a new species from Uganda. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 4960 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 196 records from Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from New species of the genus Gnathochorisis Förster (Hymenoptera: Ichneumonidae: Orthocentrinae) from the Neotropical Region. 150 records from Abundance of algae in the Aral Sea. 8 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 6 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 3465 records from Lizard Island Research Station. 12 records from Naturerfahrung. 4 records from Review of the Canadian Eustrophinae (Coleoptera, Tetratomidae). 29 records from Hidden diversity of giant scydmaenines: five new species and new records of Clidicus in the Philippines (Coleoptera, Staphylinidae, Scydmaeninae). 19580 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 98 records from Données naturalistes de Damien Combrisson. 18 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 92 records from Range table from benthic foraminifers in ODP Hole 159-962D. 1412 records from Inventory of plant species through Benin (West Africa). 17 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 472 records from South Caribbean Diversity. 42 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 178 records from Data on agroforestry plant species of Benin. 3 records from Insectes Hyménoptères Formicidés de Corse. 11 records from Radiolaria specimens from Korsfjorden Nov 1969 - May 1971. 408 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 16 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 131 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 878 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 418 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 25 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 3 records from A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae). 4 records from Bacterias aisladas de líquenes en el PNN Chingaza. 7 records from Benthic macrofauna abundance of sediment core 13078-013. 10856 records from Heteroptera collections of SW Finland. 5 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 1294 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 17 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 360 records from
Keywords: GBIF; biodiversity; species occurrences